(untitled)
The use of the Enterprise Resource Planning Systems (hereafter, ERPS) in India showed a significant growth. This growth has lead to the need to have an empirical evidence about the accounting benefits from using that systems. The existences of accounting research on ERPS has created an opportunity for further research on the Accounting Information Systems (AIS) quality and effectiveness in the decision making process related to the level of the use of the ERPS. This research is using alternative methods of Partial Least Square (PLS